PENGARUH PROMOSI, MOTIVASI BELANJA HEDONIS DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING DI MATAHARI DEPARTMENT STORE-HARTONO MALL YOGYAKARTA - Nisa', Zahrotun; Nuvriasari, Audita (LPPM STIE YKPN Yogyakarta, 2022)
This study aims to analyze Promotion, Hedonic Shopping Motivation and Store Atmosphere on Impulse Buying at Matahari Department Store-Hartono Mall Yogyakarta. The sample in this study were 100 respondents who were making purchases at Matahari Department Store-Hartono Mall Yogyakarta. The data collection technique used was a survey method with the research instrument used was a questionnaire. Instrument test results stated that the data in this study proved valid and reliable. In the Classical Assumptions Test it was stated that the data in this study were normally distributed and produced a regression model that was free from multicollinearity, heteroscedasticity, and autocorrelation. The results of this study prove that: (1) Promotion has no significant effect on Impulse Buying at Matahari Department Store-Hartono Mall Yogyakarta, (2) Hedonic Shopping Motivation has a positive and significant effect on Impulse Buying at Matahari Department Store-Hartono Mall Yogyakarta, (3) Store Atmosphere has no significant effect on Impulse Buying at Matahari Department Store-Hartono Mall Yogyakarta, (4) Promotion, Hedonic Shopping Motivation and Store Atmosphere simultaneously have a positive and significant effect on Impulse Buying at Matahari Department Store-Hartono Mall Yogyakarta. These results have implications for future researchers to use variables other than Promotion and Store Atmosphere in order to enrich what factors influence Impulse Buying. The findings of this study have implications for companies to create more attractive promotional programs and redesign store atmospheres so as to be able to influence consumer impulse buying. Key Word: Promotion, Hedonic Shopping Motivation, Store Atmosphere, Impulse Buying